In vitro and in vivo investigations on anti-influenza effect of adamantyl (alkyl, cycloalkyl) derivatives of aminopropanol-2 - Voloshchuk, O.M.; Korotkiy, Y.V.; Rybalko, S.L.; Starosila, D.B.; Shirobokov, V.P. (Вiopolymers and Cell, 2017)
Aim. To establish anti-influenza activities for 8 compounds of adamantyl (alkyl, cycloalkyl) de-rivatives of aminopropanol-2 in vitro and in vivo investigations. Methods. The antiviral action of compounds was determined in vitro by reduction of infectious titer of the influenza virus in the Madin-Darby Canine Kidney (MDCK) cell culture and in vivo on the model of influenza pneu-monia in mice. Results. Three of eight studied compounds inhibit the reproduction of the influ-enza virus strain A/FM/1/47(H1N1) by more than 2 lg ID50 in the concentration range from < 0.39 µg/ml (the compounds 30 and 33) to 1.56 µg/ml (the compound 5), their chemotherapeutic indices are 256 and 16, respectively. The experiments in vivo showed that in prophylactic scheme the efficiency index (EI) of the compounds 5 and 30 is 60 %; in therapeutic scheme EI of the compounds 5 and 33 is 100 % that is two times higher, than for rimantadine. Conclusions. High chemotherapeutic indices of the compounds 30, 33 and their ability to suppress the influenza virus reproduction in the MDCK cell culture by more than 2 lg ID50 indicate the anti-influenza activity of these compounds. It has been also confirmed by in vivo experiment. Мета. Визначити антигрипозну активність у 8 сполук адамантан (алкіл, циклоалкіл) похідних амінопропанолу-2 в дослідах in vitro та in vivo. Методи. Оцінку противірусної дії сполук проводили in vitro за зниженням інфекційного титру вірусу грипу на культурі клітин, та in vivo на моделі грипозної пневмонії у мишей. Результати. В досліді in vitro 3 сполуки серед 8 досліджених пригнічують репродукцію вірусу грипу штаму А/FM/1/47(H1N1) на 2 lg ID50 і більше в концентраціях від < 0,39 мкг/мл (сполуки №№ 30 і 33) до 1,56 мкг/мл (сполука № 5), їх хіміотерапевтичні індекси стосовно цього вірусу становлять 256 та 16, відповідно. В досліді in vivo при профілактичній схемі досліду сполуки №№ 5 і 30 мають індекс ефективності (ІЕ) 60 %, а при лікувальній схемі досліду ІЕ сполук №№ 5 та 33 більше ніж в два рази перевищує цей показник у ремантадину і становить 100 %. Висновки. Високі хіміотерапев-тичні індекси та здатність пригнічувати репродукцію вірусу грипу на 2 lg ID50 і більше дозволяє віднести сполуки №№ 30, 33 і 5 до таких, що проявляють протигрипозну активність. Це також підтверджено в досліді in vivo. Цель. Определить антигриппозную активность у 8 соединений адамантан (алкил, циклоалкил) производных аминопропанола-2 в экспериментах in vitro и in vivo. Методы. Противовирусное действие исследуемых соединений определяли in vitro по снижению инфекционного титра вируса гриппа в культуре клеток MDCK и in vivo на модели гриппозной пневмонии у мышей. Результаты. 3 соединения среди 8 исследованных подавляют репродукцию виру-са гриппа штамм А/FM/1/47(H1N1) на 2 lg ID50 и больше в концентрациях от < 0,39 мкг/мл (соединения №№ 30 и 33) до 1,56 мкг/мл (соединение № 5), их химиотерапевтические индексы (ХТИ) в отношении этого вируса состав-ляют 256 и 16, соответственно. В эксперименте in vivo при профилактической схеме опыта соединения №№ 5 и 30 имеют индекс эффективности (ИЭ) 60 %. ИЭ соединений №№ 5 и 33 при лечебной схеме опыта больше чем в два раза превышает этот показатель у Ремантадина и составляет 100 %. Выводы. Высокие ХТИ и способность подав-лять репродукцию вируса гриппа на 2 lg ID50 и более позволяют отнести соединения №№ 30, 33 и 5 к таким, что проявляют противогриппозную активность. Это также подтверждено в експриментах in vivo.